HIV/AIDS STADIUM III WITH OPPORTUNISTIC INFECTION - Ryan Falamy (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2015)
Acquired Immunodeficiency Syndrome (AIDS) is a collection of symptoms or diseases caused by decrease of immunity by the Human imunodeficiency virus (HIV) infection which includes family Retroviridae. The AIDS is a final stage of HIV infection. A woman, 27 years old, with chief complaint of abdominal pain since 2 months before hospital admission, the symptom followed with nausea and vomiting. Patients also complaint of on and off fever accompanied with a dry cough, mouth sores intermittently, decreased appetite, fatigue throughout the body. History of diarrhea 3-5x/day since 5 months ago and wrosen since last 2 months. The patient had a history of free sex before marriage. From a physical examination found blood pressure was 100/60 mmHg, pulse 76x/min, breathing frequency 20x/min, temperature 36,70C, increased bowel movement sounds, abdominal pain (+). On examination laboratory obtained Hb 10.2 g/dl, leukocytes 7,300/mm3, platelets 476,000/mm3, SGOT 29 U/dL, SGPT 24 U/dL, urea 25 mg/dl, creatinine 0.8 mg/dl, HIV reactive. Patient was diagnosed with HIV/AIDS stadium III with opportunistic infections. The management was bed rest, soft food high calorie high protein diet, infusion KAEN 3B XX gtt/min, paracetamol 3x500 mg tab if fever, ranitidine injection 1 amp/12 hours, ketoconazole 200 mg tab 3x1, folic acid 3x1 tab, bicarbonate 3x1 tab, cotrimoxazol2x960 mg for 2 weeks, anti-retroviral (stavudin+lamivudine+nevirapine). Once a person was infected with HIV, for lifetime he will remain infected, so it takes antiretroviral treatment for a lifetime to prevent the progression of HIV infection. [J Agromed Unila 2015; 2(1):28-31]Keywords: acquired immunodeficiency syndrome, anti-retroviral, human imunodeficiency virus, opportunistic infection